2020
DOI: 10.1021/acs.jafc.0c01209
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Microplastics in Commercial Seafood under the Perspective of the Human Food Chain. A Review

Abstract: The occurrence of microplastics in the marine ecosystem and aquatic organisms, their trophic transfer along the food web, and the identification of seafood species as suitable indicators have become a research priority. Despite the high quantity of research in this field, a comparison between the available data and an appropriate risk assessment remains difficult. In this perspective, as an innovative approach, the association of the feeding strategies of commercial seafood and the microplastic level was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(87 citation statements)
references
References 29 publications
0
66
0
3
Order By: Relevance
“…Feeding strategy can influence this intake: for example, in the South Pacific it was observed that fish selected fragments in colors corresponding to their food items (Mizraji et al, 2017;Ory et al, 2017). It has also been suggested that fish with more selective diets tend to eat less plastics than those with more generalist feeding habits; however, smaller particles can be more easily ingested irrespective of feeding strategy (Mercogliano et al, 2020). In addition, the type of habitat could also influence ingestion, since it has been shown that some fish species that occur in coastal regions closer to urbanized areas had higher plastic intake than those in less urbanized areas (Peters and Bratton, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding strategy can influence this intake: for example, in the South Pacific it was observed that fish selected fragments in colors corresponding to their food items (Mizraji et al, 2017;Ory et al, 2017). It has also been suggested that fish with more selective diets tend to eat less plastics than those with more generalist feeding habits; however, smaller particles can be more easily ingested irrespective of feeding strategy (Mercogliano et al, 2020). In addition, the type of habitat could also influence ingestion, since it has been shown that some fish species that occur in coastal regions closer to urbanized areas had higher plastic intake than those in less urbanized areas (Peters and Bratton, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The scope of macroplastic accumulation is evidenced by littered shorelines around the world. While macroplastics are the most visible components of plastic contamination very small particles, known as microplastics, may be just as important 3,12 . One of the initial observations of microplastics was in the early 1970s when small plastic particles were observed in water samples collected with a plankton net 13 .…”
mentioning
confidence: 99%
“…Plastic debris either float through the seawater column or sink when they become covered in biofilm, and settle into the sediments 6,16 . Plastic particles of all range sizes not only contain additives but also other anthropogenic contaminants, such as organic chemicals that are adsorbed from surrounding seawater 7,17 . These pollutants include persistent, bioaccumulative, and toxic substances (PBTs), such as polychlorinated biphenyls (PCBs) and dioxins.…”
mentioning
confidence: 99%